Exploring the Causal Links of Public Spending on Bank-Based Financial Development in African Economies - Kapaya, Saganga Mussa (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This work examined the causal impact of types of government spending on bank-based financial development. It tests the influences of both government productive and non-productive spending on bank-based financial development. Selected 37 African economies between 1980-2018 were sampled. Both the short –run and long –run effects were assessed using either Feasible Generalized Least Squares (FGLS), Mean Group (MG), Pooled Mean Group (PMG) and Dynamic Common Correlated Effects Mean Group (DCCEMG) estimators. Evidences support the hypotheses that both types of spending contribute positively to bank-based financial development. Bank-based financial development is more responsive to non-productive spending than it is to productive spending. Also, confirm the supportive roles of trade openness and GDP per capita, and the detriment of inflation to bank-based financial development. This study comprehensively unearths the impact of government spending on bank-based financial development in Africa by isolating spending into productive and non-productive types. Governments need to promote dual policies that address spending and financial development. They should avoid detrimental spending and promote enhancing spending within each type above. Spending that attract private agents, investments, saving, and liquidity in the financial sector, trade openness, and economic output should be promoted since these enhances bank-based financial development.